The effect of demographic factors on consumer intention to purchase organic products in the Klang Valley: an empirical study - Nor Asiah Omar,; Muhamad Azrin Nazri,; Lokhman Hakim Osman,; Mhd Suhaimi Ahmad, (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
The global market for organic food has developed significantly in the past decade. The organic food industry in Malaysia is getting wider, even though the domestic market remains relatively small. The main purpose of this study is to investigate the effect of demographic factors towards purchase intention of organic food. A total of 150 completed questionnaires was collected via convenience sampling from customers of a shopping-mall in Malaysia’s Klang Valley. Five demographic variables were used in this study, including gender, age, level of income, level of education and presence of children in the household. The findings revealed that, gender, age, level of education did have significant impacts on the consumer intention to buy organic food. These findings will appeal to those interested in consumer behaviour regarding organic food consumption and the continued development of Malaysia’s organic food industry.